Diet of Melanophryniscus paraguayensis (Anura: Bufonidae): An Endemic Species to Paraguay - Núñez, Karina (2021)
Melanophryniscus paraguayensis (no common name) is an endemic toad of the central grasslands in the eastern region of Paraguay. Details about its natural history are poorly understood and it is categorized nationally as Vulnerable. This work describes the diet composition of this species and the relationship between toad body size and the number and volume of prey consumed. We analyzed the stomach content of 162 individuals, using the stomach flushing technique, after measuring and weighing them. For each prey category, we calculated the volume, number, and frequency of occurrence, and we estimated the relative importance index (IRI) with these data. We also estimated the standardized Shannon Diversity Index and Levins Niche Breadth Index for prey categories, and we analyzed the correlation between size of the anurans and prey size. Seventy-six individuals had identifiable content, which consisted of 1,357 prey classified into 16 categories, mostly at the order level. Ants and mites were the prey taxa with the greatest contribution in number and frequency and represent the most important prey based on IRI. Volumetrically, ants and beetles predominated. Ticks, spiders, springtails, flies, true bugs, wasps, termites, thrips, larvae and nymphs of insects, centipedes, crabs, and snails were occasional prey. The mean prey volume consumed by toads was positively correlated with toad snout-vent length. The Shannon and Levins indices showed that the composition of the diet was dominated by a few groups of arthropods. This work demonstrates the importance of ants, mites, and beetles as food for M. paraguayensis, which is consistent with findings for other species of the genus Melanophryniscus and of many species of the Bufonidae family.